Linear thermo-responsive dielectric behaviors in poly(vinylidene fluoride)/ionic liquid composite fibrous films. (November 2022) - Gong, Yutie; Wu, Wenqi; Li, Zhenzhen; Zhou, Weijie; Zhao, Jiayu; Li, Qiong; Jiang, Ming; Li, Hairong
Abstract: Temperature sensors based on linear relationships between temperature and outputs are highly appreciated due to their high accuracy, simplicity, and convenience of use. However, the utility of linear response temperature sensors is restricted by the difficulties in dealing with some specific measurement requirements and synchronous realization of good linearity, low cost, and adequate vibration or impact resistance. Herein, an efficient strategy combining linear response, low cost, promising sensitivity, excellent vibration or impact resistance, as well as good adaptability to the measurements of curved temperature fields or spatial temperature in one temperature sensing material is proposed. The linear thermo-responsive poly(vinylidene fluoride)/ionic liquid composite fibrous films are constructed at room temperature by the solution blow spinning, providing an efficient, continuous, low-energy, and low-cost fabrication pathway and ensuring the satisfactory flexibility to withstand vibration or impact. The electrode and interfacial polarizations under strong interaction constraints of the fiber matrix contributes to a good linear dielectric response relationship between the temperature and dielectric constant, resulting in R-square up to 0.99981. The dipole polarization capability promoted by the high polar phase ratio of PVDF improves its temperature sensitivity. Specifically, the linear dielectric response relationship exhibits an important frequency dependence, allowing the temperature response sensitivity to be adjusted and improved by frequency. Meanwhile, the fibrous films also show excellent stability and repeatability over 100 thermal cycles. This work provides a novel route to design and fabricate linear response temperature sensing materials. Graphical abstract: Image 1 Highlights: PVDF/IL composite fibrous films are constructed by efficient, continuous, and low-cost solution blow spinning. PVDF/IL composite fibrous films present high dielectric-temperature linearity of with R-square up to 0.99981. PVDF/IL composite fibrous films allow the temperature response sensitivity to be readily adjusted by frequency. PVDF/IL composite fibrous films exhibit excellent stability and repeatability over 100 thermal cycles.